2018
DOI: 10.1111/jmi.12692
|View full text |Cite
|
Sign up to set email alerts
|

Automatic deformable registration of histological slides to μCT volume data

Abstract: Localizing a histological section in the three-dimensional dataset of a different imaging modality is a challenging 2D-3D registration problem. In the literature, several approaches have been proposed to solve this problem; however, they cannot be considered as fully automatic. Recently, we developed an automatic algorithm that could successfully find the position of a histological section in a micro computed tomography (μCT) volume. For the majority of the datasets, the result of localization corresponded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
(137 reference statements)
0
13
0
1
Order By: Relevance
“…Because of this, we used a mutual information-based registration approach, rather than a landmark based method. Chicherova et al demonstrated successful registration between microCT and histology in 3D using a SURF (Speeded Up Robust Features) algorithm 40 . Since SURF is based on the automatic identification of corresponding landmarks, it appears to work well on histochemical stainings such as the HE staining presented in their publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, we used a mutual information-based registration approach, rather than a landmark based method. Chicherova et al demonstrated successful registration between microCT and histology in 3D using a SURF (Speeded Up Robust Features) algorithm 40 . Since SURF is based on the automatic identification of corresponding landmarks, it appears to work well on histochemical stainings such as the HE staining presented in their publication.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to further evaluate whether the registration quality can be improved by forfeiting the assumption that the microtome cuts strictly on a plane. Additionally, Chicherova et al settled on a deformation model based on Legendre-polynomials in order to avoid the flexibility of the b-splines 40 . This is indeed a reasonable approach when applied in dense tissues like bone and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches for microCT and histology co-registration were presented by others. Chicherova et al demonstrated successful registration between microCT and histology in 3D using a SURF (Speeded Up Robust Features) algorithm 36 . Since SURF is based on the automatic identi cation of corresponding landmarks, it appears to work well on histochemical stainings such as the HE staining presented in their publication.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to further evaluate whether the registration quality can be improved by forfeiting the assumption that the microtome cuts strictly on a plane. Additionally, Chicherova et al settled on a deformation model based on Legendre-polynomials in order to avoid the exibility of the b-splines 36 . This is indeed a reasonable approach when applied in dense tissues like bone and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…For such a comparison, one needs powerful registration algorithms [48]. N. Chicherova et al performed dedicated research activities for the non-rigid slice-to-volume registration as required for the identification of the counterparts of histology slides within CT-data [49][50][51]. This task is particularly challenging due to the many degrees of freedom [52].…”
Section: Imaging Biological Cells Using Hard X-ray Tomographymentioning
confidence: 99%